Pengaruh Kualitas Barang Dan Harga Terhadap Keputusan Pembelian Pada Toko Vei Baby Kids Manna Bengkulu Selatan - Ningtias, Marisa Ayu; Handayani , Sri; Subhi, Ramadan (Sekolah Tinggi Ilmu Ekonomi Bentara Persada, 2024)
In the world of the clothing business, especially clothing for babies, a shop must be more active in marketing and improving the quality of goods. The purpose of this research is to determine the influence of product quality and price on purchasing decisions at the Vei Baby Kids Manna Store, South Bengkulu. The analytical method in this research uses Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression Analysis, Coefficient of Determination, and hypothesis testing using t test and f test with the total sample studied being 67 buyers of goods at the Vei Baby Kids Manna Store. From the results of calculations using SPSS 24, we can see that the quality of goods and price have a significant influence on purchasing decisions. In this case, the significance value of the variable X <0.05, namely 0.000. The results of the multiple linear regression analysis are the equation Y = 9.319 + 0.371 Kids Manna South Bengkulu. The value of the coefficient of determination from the calculation results using SPSS can be seen from the coefficient of determination from R square of 0.686. This means that the value of the Product Quality (X1) and Price (X2) variables influences the purchasing decision variable (Y) by 68.6% while the remaining 31.4% is influenced by other variables.